Hen’s egg as a source of valuable biologically active substances - Zygmunt Zdrojewicz (Postępy Higieny i Medycyny Doświadczalnej, 2016)
The aim of this article is to show current knowledge concerning valuable substances biologically active present in hen eggs and underline important nutritive role of hen eggs. Hen egg is a good source of nutrients such as proteins, vitamins (A, B2, B6, B12, D, E, K), minerals and lipids. The significant part of lipids is a group of unsaturated phospholipids, which are components of cell membranes, act protectively on the cardiovascular system and contribute to a decrease of cholesterol level and blood pressure. Therefore, the consumption of unsaturated phospholipids is recommended especially in patients suffering from diseases of the cardiovascular system. Another important substance is egg cystatin, which has a wide spectrum of biological functions, for example the ability to stimulate cell growth, inhibit inflammatory processes and has antibacterial and antiviral properties. Other substance presented in the egg white which helps fight bacteria is lysozyme. It is used in medicine as an aid in antibiotic therapy and analgesic in the course of infection, as well as in tumor malignancies. Among the components contained in the egg yolk there is also immunoglobulin Y which due to its therapeutic importance deserves special attention. Its use offers the possibility of replacing chemotherapeutic agents in the treatment of bacterial infections of digestive system, as well as an opportunity for the development of medicine associated with passive immunization of patients. The egg is a rich source of retinol which gradual depletion in the organism causes many eye pathologies. A very important and useful part of the egg, used in medicine is a shell and its membranes, due to the high collagen content relevant in the treatment of connective tissue diseases.